2023
DOI: 10.3390/pharmaceutics15041302
|View full text |Cite
|
Sign up to set email alerts
|

Improved Tumor Control Following Radiosensitization with Ultrasound-Sensitive Oxygen Microbubbles and Tumor Mitochondrial Respiration Inhibitors in a Preclinical Model of Head and Neck Cancer

Abstract: Tumor hypoxia (oxygen deficiency) is a major contributor to radiotherapy resistance. Ultrasound-sensitive microbubbles containing oxygen have been explored as a mechanism for overcoming tumor hypoxia locally prior to radiotherapy. Previously, our group demonstrated the ability to encapsulate and deliver a pharmacological inhibitor of tumor mitochondrial respiration (lonidamine (LND)), which resulted in ultrasound-sensitive microbubbles loaded with O2 and LND providing prolonged oxygenation relative to oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…84 In a mouse head and neck squamous cell carcinoma tumor model, a novel ultrasound-sensitive microbubble loaded with oxygen and a pharmacological inhibitor of tumor mitochondrial respiration (lonidamine (LND)) was used to successfully sensitize tumors to radiation. 85 Ultrasound-sensitive microbubbles loaded with oxygen and LND provided prolonged oxygenation relative to oxygenated microbubbles alone, as well as provided an ability to locally deliver LND, making them more appropriate for clinical translation. 86 While these studies were conducted in immunocompromised mice, future work will focus on larger immunenormal animals to evaluate the clinical relevance of the platform.…”
Section: Ultrasound-mediated Targeted Radiosensitizers Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…84 In a mouse head and neck squamous cell carcinoma tumor model, a novel ultrasound-sensitive microbubble loaded with oxygen and a pharmacological inhibitor of tumor mitochondrial respiration (lonidamine (LND)) was used to successfully sensitize tumors to radiation. 85 Ultrasound-sensitive microbubbles loaded with oxygen and LND provided prolonged oxygenation relative to oxygenated microbubbles alone, as well as provided an ability to locally deliver LND, making them more appropriate for clinical translation. 86 While these studies were conducted in immunocompromised mice, future work will focus on larger immunenormal animals to evaluate the clinical relevance of the platform.…”
Section: Ultrasound-mediated Targeted Radiosensitizers Deliverymentioning
confidence: 99%
“…The OS MBs are tested in nasopharyngeal carcinoma (CNE2) tumor‐bearing mice and oxygen delivery by the OS MBs induced by ultrasound irradiation has notable effects in reversing hypoxia and radiosensitization 84 . In a mouse head and neck squamous cell carcinoma tumor model, a novel ultrasound‐sensitive microbubble loaded with oxygen and a pharmacological inhibitor of tumor mitochondrial respiration (lonidamine (LND)) was used to successfully sensitize tumors to radiation 85 . Ultrasound‐sensitive microbubbles loaded with oxygen and LND provided prolonged oxygenation relative to oxygenated microbubbles alone, as well as provided an ability to locally deliver LND, making them more appropriate for clinical translation 86 .…”
Section: Application Strategies Of Lius In Radiosensitizationmentioning
confidence: 99%
“…In this special issue we have eight original research contributions highlighting the breadth of targets for cavitation-enhanced therapies, including Imran et al [ 1 ]. (pancreas), Lacerda et al [ 2 ] (head and neck cancer), and Ahmed et al [ 3 ] (brain), who all discuss progress in fighting long-challenging pathologies. Imran et al demonstrated substantially enhanced drug uptake in a porcine pancreatic tumor model using the SonoTran system, which is currently in a clinical trial for targeted chemotherapy to liver tumors.…”
mentioning
confidence: 99%